Find the value of a and b so that p(x)=x3-10x2+ax+b is divisible by x-1 as well as x-2
Answers
Answered by
3
Heya !!!
(X -1) and (X-2) are the two zeroes of the given polynomial.
X -1 = 0
X = 1
And,
X -2 = 0
X = 2
P(X) = X³ - 10X² + AX + B
P(1) = (1)³ - 10 × (1)² + A × 1 + B
=> 1 - 10 × 1 + A + B = 0
=> 1 - 10 + A + B = 0
=> A + B = 9 --------(1)
Also X = 2
P(2) = (2)³ - 10 × (2)² + A × 2 + B
=> 8 - 10 × 4 + 2A + B
=> 8 - 40 + 2A + B = 0
=> 2A + B = 32 ------(2)
From equation (1) we get,
A + B = 9
A = 9 - B
Putting the value of B in equation (2) we get,
2A + B = 32
2 × (9-B) + B = 32
18 - 2B + B = 32
-B = 32 -18
-B = 14
B = -14
Putting B = -14 in equation (3).
A = 9 - B => 9 - (-14)
A = 9 +14 = 23
Hence,
A = 23 and B = -14.
HOPE IT WILL HELP YOU...... :-)
(X -1) and (X-2) are the two zeroes of the given polynomial.
X -1 = 0
X = 1
And,
X -2 = 0
X = 2
P(X) = X³ - 10X² + AX + B
P(1) = (1)³ - 10 × (1)² + A × 1 + B
=> 1 - 10 × 1 + A + B = 0
=> 1 - 10 + A + B = 0
=> A + B = 9 --------(1)
Also X = 2
P(2) = (2)³ - 10 × (2)² + A × 2 + B
=> 8 - 10 × 4 + 2A + B
=> 8 - 40 + 2A + B = 0
=> 2A + B = 32 ------(2)
From equation (1) we get,
A + B = 9
A = 9 - B
Putting the value of B in equation (2) we get,
2A + B = 32
2 × (9-B) + B = 32
18 - 2B + B = 32
-B = 32 -18
-B = 14
B = -14
Putting B = -14 in equation (3).
A = 9 - B => 9 - (-14)
A = 9 +14 = 23
Hence,
A = 23 and B = -14.
HOPE IT WILL HELP YOU...... :-)
Answered by
0
One factor, x - 1
x - 1 = 0
x = 1
---------
Taking x as 1,
x³ - 10x² + ax + b = 0
=> 1³ - 10(1)² + a(1) + b(1) = 0
=> 1 - 10 + a + b =0
=> -9 +a + b = 0
=> a + b = 9 -----1equation
×××××××××××××××××
Other factor, x - 2
x - 2 = 0
x = 2
----------
Taking x as 2
x³ - 10x² + ax + b = 0
=> (2)³ - 10(2)² + a(2) + b = 0
=> 8 - 40 + 2a + b = 0
=> -32 + 2a + b = 0
=> 2a + b = 32 -------2equation
××××××××××××××××××××××
Subtract eq(2) from eq(1),
a + b = 9
2a + b = 32
(-)_(-) __(-)
-a = -23
_________
a = 23
==================
Putting the value of a in 1equation,
a + b = 9
23 + b = 9
b = 9 - 23
b = -14
=========================
Then, a = 23 and b = -14
I hope this will help you
. (-:
x - 1 = 0
x = 1
---------
Taking x as 1,
x³ - 10x² + ax + b = 0
=> 1³ - 10(1)² + a(1) + b(1) = 0
=> 1 - 10 + a + b =0
=> -9 +a + b = 0
=> a + b = 9 -----1equation
×××××××××××××××××
Other factor, x - 2
x - 2 = 0
x = 2
----------
Taking x as 2
x³ - 10x² + ax + b = 0
=> (2)³ - 10(2)² + a(2) + b = 0
=> 8 - 40 + 2a + b = 0
=> -32 + 2a + b = 0
=> 2a + b = 32 -------2equation
××××××××××××××××××××××
Subtract eq(2) from eq(1),
a + b = 9
2a + b = 32
(-)_(-) __(-)
-a = -23
_________
a = 23
==================
Putting the value of a in 1equation,
a + b = 9
23 + b = 9
b = 9 - 23
b = -14
=========================
Then, a = 23 and b = -14
I hope this will help you
. (-:
Similar questions